2020
DOI: 10.1088/1674-4527/20/7/110
|View full text |Cite
|
Sign up to set email alerts
|

Chaos and Periodicities in Solar Flare Index from Kandilli Observatory during 1976–2014

Abstract: The Solar Flare Index is regarded as one of the most important solar indices in the field of solarterrestrial research. It has the maximum effect on Earth of all other solar activity indices and is being considered for describing the short-lived dynamo action inside the Sun. This paper attempts to study the short as well as long-term temporal fluctuations in the chromosphere region of the Sun using the Solar Flare Index. The daily Solar Flare Index for Northern, Southern Hemisphere and Total Disk are considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…About 150 days periodicity detected in our study from the whole disc FI data is the Rieger periodicity which was first detected by [14] from the X-ray flare data. It was also detected by [5] as 152 days from the FI data and they argue that this periodicity appears due to the magnetic Rossby waves. Recently, Kilcik et al [30] found the same periodicity from the MCMESI and different class X-ray solar flare data.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…About 150 days periodicity detected in our study from the whole disc FI data is the Rieger periodicity which was first detected by [14] from the X-ray flare data. It was also detected by [5] as 152 days from the FI data and they argue that this periodicity appears due to the magnetic Rossby waves. Recently, Kilcik et al [30] found the same periodicity from the MCMESI and different class X-ray solar flare data.…”
Section: Discussionmentioning
confidence: 84%
“…e well-known periodic variations are the 27-day synodic rotation and 11-year Schwabe Cycle due to solar internal dynamo [9,13]. Apart from these two, the 51-, 75-, 154-, and 323-day and 1.3-, 1.8-, and 3.5-year periodicities are also reported in the literature [5,10,12,[14][15][16].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations